Influence of masonry infill on fundamental natural frequency of 2D RC frames - Chethan, K.; Babu, R. Ramesh; Venkataramana, Katta; Sharma, Akanshu (Journal of Structural Engineering, 2025)
Reinforced Concrete (RC) framed structures with Un-Reinforced Masonry (URM) infill panels form a major portion of all the RC framed structures worldwide. The URM panels are considered as non-structural members, which is fairly good assumption under gravity loads, however, it is not the same under lateral forces. Under seismic loads, the stiffness additions due to infill panels modify the dynamic behavior of the structure significantly by altering the frequency of the structure. A research project has been taken up at Earthquake Engineering and Vibration Research Centre (EVRC), Central Power Research Institute (CPRI), Bangalore to investigate the influence of masonry infill on fundamental natural frequency of RC frames. 2D RC frames of one bay and two bay having single storey, double storey and three storeys are cast and tested for bare frame and many combinations of URM infill panels. Tri-axial shake table is used for testing. The details of the numerical analysis and experimentation carried out in the research project are brought out in this paper.